Efektivitas Flipped Classroom Terhadap Sikap Dan Ketrampilan Belajar Matematika Di Smk - Damayanti, Herry Novis; Sutama, Sutama (Jurnal Manajemen Pendidikan, 2016)
The aim of the research is developed attitude resposiility, and skill learning of mathematic teaching based Flipped Classroom. The final result of the research is to taste effectiveness of mathematic teaching model based Flipped Classroom. The research method is research and development that includes introduction, field study of teaching management in the school, planning and preparing Flipped Classroom model, implementation of teaching first cycle, second cycle, and third cycle, and exam of attitude, skill, and learning outcome. Â The average result of creativity was increased with 1,84 in the eleventh grade student in PM 1 class and 1,30 in TSM 1 class. For the responsibility, in the eleventh grade student in PM 1 class was 1,84 and 1,57 for TSM 1 class in the skill aspect also increased with 1,09 in XI PM 1 class, 1,53 in XI TSM 1 class. The result of the study was determined effectiveness of the model based attitude and skill. The effectiveness was used nnon parametric Man-Whitney test for attitude and skills show that level of significant was smaller from 0,05 to 0,003; 0,008; 0,009. The research concluded that the implementation of mathematic teaching model based Flipped Classroom at the eleventh grade student of SMKN 1 Gedangsari Gunungkidul was effective.